Thomas Jefferson and the Tripoli pirates [compact disc, unabridged] : the forgotten war that changed American history - Kilmeade, Brian; Yeager, Don (Penguin Audio, 2015)
This is the little-known story of how a newly independent nation was challenged by four Muslim powers and what happened when America's third president decided to stand up to intimidation. When Thomas Jefferson became president in 1801, America faced a crisis. The new nation was deeply in debt and needed its economy to grow quickly, but its merchant ships were under attack. Pirates from North Africa's Barbary Coast routinely captured American sailors and held them as slaves, demanding ransom and tribute payments far beyond what the new country could afford. So President Jefferson decided to move beyond diplomacy. He sent the U.S. Navy's new warships and a detachment of marines to blockade Tripoli, launching the Barbary Wars and beginning America's journey toward future superpower status.